La relació del Diccionario valenciano-castellano (1851) de Josep Escrig amb la lexicografia espanyola decimonònicas. - GUARDIOLA SAVALL, M. ISABEL (Scripta)
The Diccionario valenciano-castellano (1851) by Josep Escrig is considered the first general and systematic dictionary of Valencian. In this research we will outline the degree of utilization of the Spanish lexicographical tradition that Escrig had at his disposal for the preparation of his dictionary and which he himself acknowledges in the prologue: «Al redactarle he seguido el método mismo que observa el de la Academia española».